2019
DOI: 10.1186/s13256-019-1969-z
|View full text |Cite
|
Sign up to set email alerts
|

Pantoea dispersa bacteremia in an immunocompetent patient: a case report and review of the literature

Abstract: BackgroundPantoea is a Gram-negative, non-encapsulated, non-spore-forming, ubiquitous straight rod which can be isolated from geographical and ecological sources such as plant surfaces, buckwheat seeds, human feces, and the environment. The genus Pantoea is a rare pathogen in a clinical setting, and is divided into 20 different species such as Pantoea agglomerans, Pantoea ananatis, Pantoea deleyi, Pantoea dispersa, Pantoea septica, Pantoea stewartii or Pantoea rwandensis. Pantoea dispersa has been reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 7 publications
(16 reference statements)
1
22
0
Order By: Relevance
“…The genus Pantoea has been generally found in plant surfaces as well as human feces. Some species have also been reported as human pathogens leading to bacteremia [ 62 ]. The existence of mammal microbial flora on Assam tea leaves indicates the close relationship between human, animals, and Assam tea plants.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Pantoea has been generally found in plant surfaces as well as human feces. Some species have also been reported as human pathogens leading to bacteremia [ 62 ]. The existence of mammal microbial flora on Assam tea leaves indicates the close relationship between human, animals, and Assam tea plants.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that some non-pathogenic species of human microflora are isolated from BSIs in immunocompetent patients: Gemella morbillorum was isolated from a healthy 5-month-old baby [ 26 ], Pantoea dispersa from an immunocompetent 38-year-old woman [ 27 ], Rothia mucilaginosa from a 9-month-old baby [ 28 ], and Brevibacterium paucivorans from an older patient [ 29 ]. Some species described so far as rare pathogens emerge more and more frequently in BSI and are becoming significant human pathogens, such as Kocuria rhizophila isolated from catheter-related BSIs [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pantoea dispersa has been described as an opportunistic or secondary pathogen; therefore, infections are likely to be very mild or self-limiting in most individuals (35). Nevertheless, recent studies have revealed the presence of this pathogen in health care settings (3,4,20,32,34,36), where it has been associated with various pathologies including lung infection, bacteremia, neonatal infections, and septicemia. Hence, caution should be exercised during the handling of LMFs in neonatal care, health care settings, and homes for the elderly.…”
Section: Discussionmentioning
confidence: 99%